If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 3(2p + -2) = 3p + 4 Reorder the terms: 3 + 3(-2 + 2p) = 3p + 4 3 + (-2 * 3 + 2p * 3) = 3p + 4 3 + (-6 + 6p) = 3p + 4 Combine like terms: 3 + -6 = -3 -3 + 6p = 3p + 4 Reorder the terms: -3 + 6p = 4 + 3p Solving -3 + 6p = 4 + 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. -3 + 6p + -3p = 4 + 3p + -3p Combine like terms: 6p + -3p = 3p -3 + 3p = 4 + 3p + -3p Combine like terms: 3p + -3p = 0 -3 + 3p = 4 + 0 -3 + 3p = 4 Add '3' to each side of the equation. -3 + 3 + 3p = 4 + 3 Combine like terms: -3 + 3 = 0 0 + 3p = 4 + 3 3p = 4 + 3 Combine like terms: 4 + 3 = 7 3p = 7 Divide each side by '3'. p = 2.333333333 Simplifying p = 2.333333333
| 6-4x=-5x+9 | | 7b-18.3=16.5 | | x+102+95x=180 | | 7(-2x+6)=-70 | | 5x-2(-x)-3x=3x+7 | | 12x=14+5x | | 6x-14=32+4x | | 13x^2-18x=63 | | 5(2-4x)+4x=10 | | -4n=-20.8 | | 7(1-4x)+3x=7 | | -10y+8=-3(5y-7)+5y | | 34=-2-(9n) | | 38-4p=2-2p | | 8x+28=8x-10 | | -8x-9=9x-1 | | s=2(-6+3) | | -2(t+7)=0 | | 2.5=.5a | | 6x+19+95x=180 | | -6-8=-5+x | | a^2+7a-30=equation | | 7-2c=-1.875(-2x-0.6) | | a^2+7-30=equation | | 8x+5=5n-13 | | .9a=45 | | -3(r+5)=-35 | | 3x-1-9=0 | | -x+9=x+3 | | 115x+18x+7=180 | | s=2(s+3) | | 4x-32x+7=225 |